PERANCANGAN SISTEM INFORMASI MONITORING GARDU DISTRIBUSI DI PT PLN (PERSERO) ULP AMPERA - Ronal Yudiarta; Muhamad Kadafi (Jurnal Riset Teknik Komputer, 2026)
This study aims to design a distribution substation monitoring information system at PT PLN (Persero) ULP Ampera to improve the effectiveness, efficiency, and accuracy of monitoring activities that were previously carried out manually. The main problems identified include delays in disturbance detection, data recording errors, and lack of information integration, which affect decision-making processes and service quality. The research employed the User Centered Design (UCD) method, which places users at the center of every stage of system development. The research process involved field observations, interviews with Distribution Substation Administrators, solution design, prototype development using Figma, and iterative design evaluations with users. The results indicate that the designed system successfully provides secure login features, interactive monitoring dashboards, integrated substation data management, analytical data visualization, and a location-based substation map with operational status indicators. The system also offers a simple, responsive, and user-friendly interface that supports real-time monitoring and more efficient data management. Based on the evaluation results, the web-based distribution substation monitoring information system successfully meets user operational needs and supports digital transformation efforts within PT PLN (Persero) ULP Ampera.